Restitusi Sebagai Hukuman Tambahan Yang Bermanfaat Bagi Pelaku dan Korban Tindak Pidana - Andreas Lucky Lukwira (Deviance Jurnal kriminologi, 2017)
Philosophy of utilitarianizm sees the advantage of  the punishment. Advantages for the offender, and also advantages for the society.  Imprisonment is one way that punishment can give the advantages.But in the actual time, cause adverse effects for the offenders. The deinstitutionalization school became the answer to criticism of the previous punishment school, resosialitation school and social reintegration school.In the other side,  the rights of victims began to receive attention. Among them are the right to get restitution. So the punishment that give advantage for offenders and victims can be realized.This research using descriptive analysis with literature study.